2017
DOI: 10.1016/j.jad.2016.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Mother-child bed-sharing trajectories and psychiatric disorders at the age of 6 years

Abstract: BackgroundLittle is known about the effect of bed-sharing with the mother over the child mental health.MethodsPopulation-based birth cohort conducted in Pelotas, Brazil. Children were enrolled at birth (n=4231) and followed-up at 3 months and at 1, 2, 4, and 6 years of age. Bed-sharing was defined as “habitual sharing of the bed between the child and the mother, for sleeping, for part of the night or the whole night”. Trajectories of bed sharing between 3 months and 6 years of age were calculated. Mental healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
1
12
1
Order By: Relevance
“…The lack of significant difference in children's behavioral problems found in this study between the cosleeping and non‐cosleeping groups is not consistent with previous findings that showed that cosleeping children had increased psychiatric disorders and internalizing problems (Santos et al., ) and more behavioral and emotional problems (Cortesi et al., ) when compared to non‐cosleeping children. This difference may be due to different study samples.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The lack of significant difference in children's behavioral problems found in this study between the cosleeping and non‐cosleeping groups is not consistent with previous findings that showed that cosleeping children had increased psychiatric disorders and internalizing problems (Santos et al., ) and more behavioral and emotional problems (Cortesi et al., ) when compared to non‐cosleeping children. This difference may be due to different study samples.…”
Section: Discussioncontrasting
confidence: 99%
“…In the United States, where there are no warm floors, Korean American mothers maintain cosleeping with their child on beds. The finding that the younger the child the higher the cosleeping frequency is consistent with existing evidence from the Netherlands (Luijk et al., ), Brazil (Santos et al., ), Italy (Cortesi et al., ), and Korean families in Korea (Yang & Hahn, ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations